Keluarga Sakinah Menurut Jamaah Tablig - sakirman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
The sakinah (harmonious) family is the ideal family that every family dreams of. To build a sakinah family, it requires selective efforts, including choosing a candidate of wife/husband, holding engagement, organizing wedding, and running successful households. This present research focuses on the study of a sakinah family according to Jama’ah Tablig (JT), an ideological movement, deeming that JT attempts to realize the teachings of Islam consistently in accordance with the teachings that were modeled by the Prophet Muhammad (PBUH). For this reason, what is done by JT is not in line with the current era, especially the issues related to the balance between the rights and obligations in a family. It was library research and supported with interviewing some JT members. The research results reveal that the concept of a sakinah family in the JT members’ perspectives was not much different from the concept asserted in Islamic law. Nonetheless, the concept that was stated by the JT members was more textual in understanding the concept of a sakinah family in the nash (the Qur’an and Hadith).